A survey of therapeutic drug monitoring services in Malaysia - Ab Rahman, Ab Fatah (2012)
In Malaysia, therapeutic drug monitoring (TDM) service was started in the 1980s. Since then, the number of hospitals that offer the service has increased. In this paper, we report the findings of a nationwide survey describing the practice of TDM in these hospitals. Questionnaires were mailed to 128 government hospitals. Data were collected for general characteristics of the hospitals, administrative, and laboratory activities related to TDM service. One hundred and twenty-one hospitals responded to the survey. Thirty-four hospitals (28.1%) provided the service with their own TDM laboratories, 44 hospitals (36.4%) provided the service using other hospitals’ laboratories and 43 hospitals (35.5%) did not provide the service at all. TDM services were more likely to be offered in larger hospitals with various medical specialties. Since it is managed entirely by hospital pharmacists, these pharmacists assume an important role in ensuring optimum use of the TDM service.